Assessing compatibility of excipients selected for a sustained release formulation of bilberry leaf extract - Tetiana Kolisnyk; Olga Vashchenko; Olena Ruban; Nataliya Fil; Galina Slipchenko (Universidade de São Paulo, 2022)
Abstract The study is aimed to assess the compatibility of bilberry leaf powder extract (BLPE) with six excipients selected for sustained-release (SR) tablet formulation. The BLPE was obtained with the addition of L-arginine and Myo-inositol as the carriers. Thermogravimetric (TG-DTG) analysis and Fourier-transform infrared spectroscopy (FTIR), supported by Pearson correlation analysis, were applied to detect possible interactions in the binary mixtures (1:1) of the BLPE with each excipient. The TG-DTG showed some deviations in the thermal behavior of the BLPE / excipient mixtures. However, only the thermal behavior of magnesium stearate in the mixture significantly differed from individual samples, which suggested chemical interaction for this excipient. The FTIR analysis confirmed that the BLPE is compatible with Eudragit L100, Methocel K4M, Methocel K100LV, Avicel PH-101, and Plasdone S-630. Whereas it undergoes solid-state chemical interaction in the binary mixture with magnesium stearate. According to the FTIR-spectra, it is suggested that this interaction results in the formation of stearic acid and alkalization of the medium. These findings evidence for the possibility of using TG-DTG analysis as an independent thermal technique for compatibility studies and also confirm the earlier reported interaction of basic lubricants, e.g., stearic salts, with active ingredients containing amino groups.